Longitudinal analysis of new multiple sclerosis lesions with magnetization transfer and diffusion tensor imaging - Gloor, Monika; Andelova, Michaela; Gaetano, Laura; Papadopoulou, Athina; Burguet Villena, Federico; Sprenger, Till; Radue, Ernst-Wilhelm; Kappos, Ludwig; Bieri, Oliver; Garcia, Meritxell (European radiology, 2024)
OBJECTIVE: The potential of magnetization transfer imaging (MTI) and diffusion tensor imaging (DTI) for the detection and evolution of new multiple sclerosis (MS) lesions was analyzed. METHODS: Nineteen patients with MS obtained conventional MRI, MTI, and DTI examinations bimonthly for 12 months and again after 24 months at 1.5 T MRI. MTI was acquired with balanced steady-state free precession (bSSFP) in 10 min (1.3 mm3 isotropic resolution) yielding both magnetization transfer ratio (MTR) and quantitative magnetization transfer (qMT) parameters (pool size ratio (F), exchange rate (kf), and relaxation times (T1/T2)). DTI provided fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD). RESULTS: At the time of their appearance on MRI, the 21 newly detected MS lesions showed significantly reduced MTR/F/kf and prolonged T1/T2 parameters, as well as significantly reduced FA and increased AD/MD/RD. Significant differences were already observed for MTR 4 months and for qMT parameters 2 months prior to lesions' detection on MRI. DTI did not show any significant pre-lesional differences. Slightly reversed trends were observed for most lesions up to 8 months after their detection for qMT and less pronounced for MTR and three diffusion parameters, while appearing unchanged on MRI. CONCLUSIONS: MTI provides more information than DTI in MS lesions and detects tissue changes 2 to 4 months prior to their appearance on MRI. After lesions' detection, qMT parameter changes promise to be more sensitive than MTR for the lesions' evolutional assessment. Overall, bSSFP-based MTI adumbrates to be more sensitive than MRI and DTI for the early detection and follow-up assessment of MS lesions. CLINICAL RELEVANCE STATEMENT: When additionally acquired in routine MRI, fast bSSFP-based MTI can complement the MRI/DTI longitudinal lesion assessment by detecting MS lesions 2-4 months earlier than with MRI, which could implicate earlier clinical decisions and better follow-up/treatment assessment in MS patients. KEY POINTS: • Magnetization transfer imaging provides more information than DTI in multiple sclerosis lesions and can detect tissue changes 2 to 4 months prior to their appearance on MRI. • After lesions' detection, quantitative magnetization transfer changes are more pronounced than magnetization transfer ratio changes and therefore promise to be more sensitive for the lesions' evolutional assessment. • Balanced steady-state free precession-based magnetization transfer imaging is more sensitive than MRI and DTI for the early detection and follow-up assessment of multiple sclerosis lesions.
Keywords: Magnetic Resonance Imaging; Diffusion tensor imaging; zobrazování difuzních tenzorů; Magnetization transfer ratio; Anisotropy; mozek; magnetická rezonanční tomografie; Multiple sclerosis; anizotropie; Humans; roztroušená skleróza; Diffusion Tensor Imaging; lidé; Quantitative magnetization transfer; Brain; Multiple Sclerosis; Balanced steady-state free precession